Implementation of the Fast Method in Android-Based New Student Registration Application - Alda, Muhamad; Sibarani, Fathiya Hasyifah (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2024)
As the information and technology sectors develop, Android smartphones are a means of disseminating information that offers many benefits. In the current era, information technology has a huge impact on every aspect of daily life. Improvements in information technology in the education sector will become more user-friendly. One of them is SMP N 5 Medan, which requires IT assistance to register new students who still use paper forms. The current system has a problem because it makes it difficult to collect data and create reports. This research aims to develop an Android application that can be used by prospective students to register and assist SMPN 5 Medan in monitoring prospective student registration data. Application development in this research uses the FAST method, which includes scope definition, problem analysis, requirements analysis, logical design, decision analysis, physical design and integration, development and testing, and delivery. The developed application facilitates information access, registration, and aids SMP N 5 Medan in generating new student registration reports.